Study of the Cu(II) Removal from Aqueous Medium Using Carbon Prepared from Licuri Shell (Syagrus coronata) - Sa, Ivero P.; Filho, Emanoel O. S.; Nascimento, Wesley G.; Ferreira, Marcio L. O.; Braga, Valdeilson S.; Estrela, Tiago dos S.; Castro, Gustavo R. [UNESP]; Amorim, Fabio A. C. (Brazilian Chemical Soc, 2017)
Different alternatives for the removal of metals in waters and effluents are used, and the adsorption is a widely used method. This study aimed to preparation of the activated carbon from the shell of licuri (Syagrus coronata) coconut (LAC) and its use for the removal of Cu (II) ions from aqueous solution by optimizing the adsorption conditions. The material was calcined, and subsequently ground and sieved, followed by chemical activation with sulfuric acid. The equilibrium experimental conditions were obtained from pH 8, temperature 25 +/- 1 degrees C, mass 100 mg of LAC, Cu (II) solution volume of 40 ml and adsorption time of 60 minutes. Under these conditions, the maximum adsorption capacity was of 26 mg g(-1) and 10 mg g(-1), respectively, for solutions containing 80 and 20 mg L-1 of Cu (II), representing a removal of 25% and 60%, respectively. Experimental data indicate better suitability for the kinetic model pseudo 2nd order (R-2 = 0.981) and adsorption isotherm best correlated to the Langmuir model (R-2 = 0.996). The results showed satisfactory efficiency for the removal Cu (II) in aqueous solutions from a simple and low cost method, using as adsorbent an agricultural residue widely produced in Brazil.
Keywords: Copper adsorption; Syagrus coronata; licuri coconut; activated carbon